Transformation of The Regional Symbol That Occurs in the Logo PERSIB and It’s Influence on Public Perception - Cahyadi, A T; Wantoro; Maulana, Y I (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Football is the most popular sport in Indonesia. People cannot be unseparated from the presence of the club's logo and visual identity while supporting, including what happened at PERSIB Bandung, which is the most popular club in Indonesia. Since the first PERSIB Bandung logo looks similar to the Bandung City Government Emblem Symbol and some people consider this to look unprofessional and outdated. But actually, PERSIB Bandung redesigned the logo in 2015. The purpose of this research is to determine the visual transformation and differences between the latest PERSIB Bandung logo and the Bandung City Government emblem Symbol. This study will use a comparative method approach by comparing visual styles, basic shapes, elements, typography, color, and layout. The final result will be strengthened by quantitative data analysis to measure public perception of the latest Bandung PERSIB logo. This research is expected to be a reference and to know the brand image of the identity of PERSIB Bandung.